2021
DOI: 10.3390/diagnostics11020260
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescence Imaging of the Skin Is an Objective Non-Invasive Technique for Diagnosing Pseudoxanthoma Elasticum

Abstract: Pseudoxanthoma elasticum (PXE) is a rare multisystemic autosomal recessive connective tissue disease. In most cases, skin manifestations of PXE are the first to develop, followed later by severe ocular and cardiovascular complications. In our present study, in addition to dermoscopy, we introduced novel techniques, autofluorescence (AF) and diffuse reflectance (DR) imaging for the assessment of affected skin sites of five PXE patients. PXE-affected skin areas in most skin sites showed a previously observed pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
0
4
0
3
Order By: Relevance
“…An LED-based MSI device was recently successfully introduced for the detection of recurring skin cancers [43,44] and proved to be applicable in the differentiation of different tumor types from benign lesions based on their mean intensity of autofluorescence (AF) [45]. In addition, MSI has been also utilized for the detection of rare skin disorders [46,47].…”
Section: Figurementioning
confidence: 99%
“…An LED-based MSI device was recently successfully introduced for the detection of recurring skin cancers [43,44] and proved to be applicable in the differentiation of different tumor types from benign lesions based on their mean intensity of autofluorescence (AF) [45]. In addition, MSI has been also utilized for the detection of rare skin disorders [46,47].…”
Section: Figurementioning
confidence: 99%
“…Our research group has previously shown this technique to differentiate seborrheic keratosis from melanoma [ 33 ]. In addition, we introduced MSI for the diagnostics of rare skin disorders, including pseudoxanthoma elasticum [ 34 ] and keratinopathic ichthyosis [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…As for the Phenodex skin scores, the absence of significant associations with T50 in the current study might be attributed to the fact that the severity of cutaneous alterations in PXE is only partially reflected by the Phenodex S score as, for example, redundant skin folds due to loss of elasticity might not always reflect higher disease activity compared to extensive papules or plaques. Future studies should, therefore, focus on novel evaluation and grading methods of skin lesion severity, for example, by implementing in vivo autofluorescence and dermoscopy techniques [42,43]. Potential associations between Phenodex cardiac and gastrointestinal scores and T50 could not be adequately evaluated in our current PXE patient population due to the low prevalence of Phenodex-scored events such as myocardial infarction or stomach bleeding.…”
Section: Discussionmentioning
confidence: 99%